Potassium secretion in rat distal colon during dietary potassium loading: role of pH regulated apical potassium channels - Sandle, G (1999)
Background—Chronic dietary K(+) loading increases the abundance of large conductance (210 pS) apical K(+) channels in surface cells of rat distal colon, resulting in enhanced K(+) secretion in this epithelium. However, the factors involved in the regulation of these K(+) channels are at present unclear.  Aims—To evaluate the effect of dietary K(+) loading on intracellular pH and its relation to large conductance apical K(+) channel activity in surface cells of rat distal colon.  Methods/Results—As assessed by fluorescent imaging, intracellular pH was higher in K(+) loaded animals (7.48 (0.09)) than in controls (7.07 (0.04); p<0.01) when surface cells were bathed in NaCl solution, and a similar difference in intracellular pH was observed when cells were bathed in Na(2)SO(4) solution (7.67 (0.09) and 6.92 (0.05) respectively; p<0.001). Ethylisopropylamiloride (EIPA; an inhibitor of Na(+)-H(+) exchange; 1 µM) decreased intracellular pH when surface cells from K(+) loaded animals were bathed in either solution, although the decrease was greater when the solution contained NaCl (ΔpH 0.50 (0.03)) rather than Na(2)SO(4) (ΔpH 0.18 (0.02); p<0.05). In contrast, EIPA had no effect in cells from control animals. As assessed by patch clamp recording techniques, the activity of large conductance K(+) channels in excised inside-out membrane patches from distal colonic surface cells of K(+) loaded animals increased twofold when the bath pH was raised from 7.40 to 7.60. As assessed by cell attached patches in distal colonic surface cells from K(+) loaded animals, the addition of 1 µM EIPA decreased K(+) channel activity by 50%, consistent with reversal of Na(+)-H(+) exchange mediated intracellular alkalinisation.  Conclusion—Intracellular alkalinisation stimulates pH sensitive large conductance apical K(+) channels in rat distal colonic surface cells as part of the K(+) secretory response to chronic dietary K(+) loading. Intracellular alkalinisation seems to reflect an increase in EIPA sensitive Na(+)-H(+) exchange, which may be a manifestation of the secondary hyperaldosteronism associated with this model of colonic K(+ )adaptation.    Keywords: colon; dietary potassium; pH; potassium channels